Characteristics, Mortality, and Clinical Outcomes of Hospitalized Patients with COVID-19 and Diabetes: A Reference Single-Center Cohort Study from Poland. (16th February 2023) - Kania, Michał; Mazur, Konrad; Terlecki, Michał; Matejko, Bartłomiej; Hohendorff, Jerzy; Chaykivska, Zlata; Fiema, Mateusz; Kopka, Marianna; Kostrzycka, Małgorzata; Wilk, Magdalena; Klupa, Tomasz; Witek, Przemysław; et al.
Abstract : Background . Diabetes is a risk factor for a severe course of COVID-19. We evaluated the characteristics and risk factors associated with undesirable outcomes in diabetic patients (DPs) hospitalized due to COVID-19. Materials and Methods . The data analysis of patients admitted between March 6, 2020, and May 31, 2021, to the University Hospital in Krakow (Poland), a reference center for COVID-19, was performed. The data were gathered from their medical records. Results . A total number of 5191 patients were included, of which 2348 (45.2%) were women. The patients were at the median age of 64 (IQR: 51–74) years, and 1364 (26.3%) were DPs. DPs, compared to nondiabetics, were older (median age: 70 years, IQR: 62–77 vs. 62, IQR: 47–72, and p  < 0.001) and had a similar gender distribution. The DP group had a higher mortality rate (26.2% vs. 15.7%, p  < 0.001) and longer hospital stays (median: 15 days, IQR: 10–24 vs. 13, IQR: 9–20, and p  < 0.001). DPs were admitted to the ICU more frequently (15.7% vs. 11.0%, p  < 0.001) and required mechanical ventilation more often (15.5% vs. 11.3%, p  < 0.001). In a multivariate logistic regression, factors associated with a higher risk of death were age >65 years, glycaemia >10 mmol/L, CRP and D-dimer level, prehospital insulin and loop diuretic use, presence of heart failure, and chronic kidney disease. Factors contributing to lower mortality were in-hospital use of statin, thiazide diuretic, and calcium channel blocker. Conclusion . In this large COVID-19 cohort, DPs constituted more than a quarter of hospitalized patients. The risk of death and other outcomes compared to nondiabetics was higher in this group. We identified a number of clinical, laboratory, and therapeutic variables associated with the risk of hospital death in DPs.